Amino acid sequence alignment of vertebrate CAPN3/calpain-3/p94 - Ono, Yasuko (Data Brief, 2015)
CAPN3 is a calpain superfamily member that is predominantly expressed in skeletal muscle. So far, clear CAPN3 orthologs were found only in vertebrates. CAPN3 is a unique protease in that it undergoes extremely rapid and exhaustive autolysis and that autolyzed fragments spontaneously associate each other to reconstitute the proteolytic activity. These unique properties of CAPN3 are dependent on IS1 and IS2, two CAPN3-characterizing sequences that do not exist in other calpains or any other proteases. To understand how IS1 and IS2 are conserved among vertebrates, this data article provides amino acid sequence alignment of representative vertebrate CAPN3s. For further analysis and discussion, see Ono et al. [1]